Diversity of Knowledge-Sharing Behavior to Encourage the Practice of Robusta Coffee Red-Picking (Case Study of Temanggung Robusta Coffee Farmer, Indonesia) - Hanifah Ihsaniyati; Sarwititi Sarwoprasodjo; Pudji Muljono; Dyah Gandasari (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Red-picking is the key to good coffee quality and is essential for increasing farmers’ income, added value, competitiveness, and development. Knowledge-sharing is one solution to improve the knowledge confidence of farmers and the reach of dissemination of red-picking practices. This research aims to determine the diversity of knowledge-sharing behavior related to red-picking practices according to farmers’ socio-economic status. This research was conducted in a constructivist paradigm with a qualitative approach and case study strategy. According to specific characteristics, seven primary informants were determined by staged, purposive, and peer group discussions. Temanggung coffee stakeholders take part as supporting informants. Interviews, focus group discussions, social media and document observations, expert discussions, peer group discussions, literature reviews, and documentation were used to collect research data. The data were analyzed qualitatively using the NVivo 12 Plus. Research has found that diversity of knowledge-sharing tends to encourage red-picking practices. The research findings also stated that group farmers with an area of land ≤ 1 ha, younger generation group farmers, group farmers with roles as gathering traders, and group farmers who use social media have more diverse knowledge-sharing behaviors. The practice of red-picking can be encouraged by supporting farmers in carrying out knowledge-sharing activities with other farmers with different characteristics. This study implies that the resulting findings will enrich the concept of knowledge-sharing by describing how people utilize social and offline media in sharing knowledge to encourage red-picking practices.